2019
DOI: 10.1007/s12119-019-09683-7
|View full text |Cite
|
Sign up to set email alerts
|

Homonationalism in Europe? A Quantitative Comparison of the Values of Europeans

Abstract: In the context of growing interest in sexual dissidence, academic and social movements are discussing homonationalism as the combination of tolerance towards lesbians and gays, racism and nationalism in a neoliberal globalised world. In this article we aim to quantitatively compare European nation states on homonationalist values using data collected through the European Value Study (2008-2010), through correlations and cross tabulation analysis. We ask to what extent homonationalism is reflected in the values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 44 publications
0
11
0
7
Order By: Relevance
“…Populist critiques of migrants have politicized the conservatism of certain migrant communities on the question of sexual minoritiesculminating in the emergence of a homonationalist discourse (Puar, 2007). Interestingly, Freude and Bosch (2020) find that Sweden has the fourthlargest homonational grouping in its population -with a high correlation between LGBT tolerance and racism.…”
Section: The Role and Power Of Global Gender Indexesmentioning
confidence: 99%
“…Populist critiques of migrants have politicized the conservatism of certain migrant communities on the question of sexual minoritiesculminating in the emergence of a homonationalist discourse (Puar, 2007). Interestingly, Freude and Bosch (2020) find that Sweden has the fourthlargest homonational grouping in its population -with a high correlation between LGBT tolerance and racism.…”
Section: The Role and Power Of Global Gender Indexesmentioning
confidence: 99%
“…Aunque en la aproximación de Puar no se conceptualizan valores homonacionalistas, en la discusión sobre homonacionalismo el either-or-split en identidades y proyecciones sobre ellos -entre otredad racial y otredad sexual -es central. Los índices propuestos, y especialmente la correlación, miden la exclusividad y exhaustividad de otredad sexual y racial en la población y profundizan así unas primeras evidencias empíricas en trabajos anteriores (Freude y Vergés Bosch, 2020;Spierings, 2020).…”
Section: Ied = Indicador Colectivo 1 / Indicador Colectivounclassified
“…Furthermore, despite a context of increasing homonationalism, European LGBTI movements themselves have developed intersectional political consciousnesses and sought coalition with other movements—including those advocating on the behalf of immigrants and Muslims (Ayoub, 2019). Others have found that although there are groups in Western Europe that combine tolerance toward LGB people with racism and nationalism, tolerance toward homosexuality generally correlated with less racist and nationalist values (Freude & Bosch, 2019). Meanwhile, Zanghellini (2012) has argued that homonationalism is conceptually useful but overused and sometimes overstated, leading it to be over‐applied both by activists and academics when examining LGBTQ + activism.…”
Section: Applications and Debates Of Scopementioning
confidence: 99%
“…The grounding in critical theory has certainly shaped current theoretical and methodological application of the concept in research. In particular, related work has overwhelmingly utilized qualitative methods (but see Freude & Bosch 2019). Understanding this background helps to contextualize how and why research on homonationalism has largely trended away from the original formulation's emphasis on practices within Western LGBTQ + groups and movements and toward an understanding of homonationalism as an emergent global discourse that legitimates inequality on a global scale.…”
Section: Current and Future Research Directionsmentioning
confidence: 99%
See 1 more Smart Citation